Compliance to the smoke-free law in Guatemala 5-years after implementation - Joaquín Barnoya; Jose C. Monzon; Paulina Briz; Ana Navas-Acien (BMC Public Health, 2016)
Abstract Background Smoke-free environments decrease smoking prevalence and consequently the incidence of heart disease and lung cancer. Due to issues related to poor enforcement, scant data is currently available from low/middle income countries on the long-term compliance to smoke-free laws. In 2006, high levels of secondhand smoke (SHS) were found in bars and restaurants in Guatemala City. Six months after a smoking ban was implemented in 2009, levels significantly decreased. However, in 2010, poor law compliance was observed. Therefore, we sought to assess long-term compliance to the ban using SHS measurements. Methods In 2014 we assessed SHS exposure using airborne nicotine monitors in bars (n = 9) and restaurants (n = 12) for 7 days using the same protocol as in 2006 and in 2009. Nicotine was measured using gas-chromatography (μg/m3) and compared to levels pre- (2006) and post-ban (2009). Employees responded to a survey about SHS exposure, perceived economic impact of the ban and customers’ electronic cigarette use. In addition, we estimated the fines that could have been collected for each law infringement. Results Most (71 %) venues still have a smoking section, violating the law. The percentage of samples with detectable nicotine concentrations was 100, 85 and 43 % in 2006, 2009 and 2014, respectively. In bars, median (25th and 75th percentiles) nicotine concentrations were 4.58 μg/m3 (1.71, 6.45) in 2006, 0.28 (0.17, 0.66) in 2009, and 0.59 (0.01, 1.45) in 2014. In restaurants, the corresponding medians were 0.58 μg/m3 (0.44, 0.71), 0.04 (0.01, 0.11), and 0.01 (0.01, 0.09). Support for the law continues to be high (88 %) among bar and restaurant employees. Most employees report no economic impact of the law and that a high proportion of customers (78 %) use e-cigarettes. A total of US$50,012 could have been collected in fines. Conclusions Long-term compliance to the smoking ban in Guatemala is decreasing. Additional research that evaluates the determinants of non-compliance is needed and could also contribute to improve enforcement and implementation of the smoke-free law in Guatemala.